1999
DOI: 10.1086/302620
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in NPC1 Highlight a Conserved NPC1-Specific Cysteine-Rich Domain

Abstract: Niemann-Pick type II disease is an autosomal recessive disorder characterized by a defect in intracellular trafficking of sterols. We have determined the intron/exon boundaries of eight exons from the conserved 3' portion of NPC1, the gene associated with most cases of the disease. SSCP analyses were designed for these exons and were used to identify the majority of mutations in 13 apparently unrelated families. Thirteen mutations were found, accounting for 19 of the 26 alleles. These mutations included eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 30 publications
6
108
0
1
Order By: Relevance
“…In our cohort of patients the mutation was also identified either in homozygosity or heterozygosity in three patients all with the variant filipin staining pattern. In homozygosity it was associated with the adult form of the disease in siblings #12 and #13, in good accordance with other studies (Ribeiro et al 2001;Stampfer et al 2013) whereas in heterozygosity with the missense mutation p.S940L(c.2819C>T) (Greer et al 1999) it was associated with juvenile onset of disease (Patient #11). Patient #14 was shown to be homozygous for the mutation IVS2+5G>A (c.190+5G>A) in the NPC2 gene.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In our cohort of patients the mutation was also identified either in homozygosity or heterozygosity in three patients all with the variant filipin staining pattern. In homozygosity it was associated with the adult form of the disease in siblings #12 and #13, in good accordance with other studies (Ribeiro et al 2001;Stampfer et al 2013) whereas in heterozygosity with the missense mutation p.S940L(c.2819C>T) (Greer et al 1999) it was associated with juvenile onset of disease (Patient #11). Patient #14 was shown to be homozygous for the mutation IVS2+5G>A (c.190+5G>A) in the NPC2 gene.…”
Section: Resultssupporting
confidence: 89%
“…In the NPC1 patients, 12 different mutations and nine different genotypes were identified. Eight of the mutations had been previously described: p.E1089K (3265G>A) (Sun et al 2001), p.F284Lfs*26 (c.852delT) (Fancello et al 2009), p. A1132P(c.3394G>C) (Mavridou et al 2014), del promoter region and exons 1-10 (Rodriguez-Pascau et al 2012), p. R1186H(c.3557G>A) (Carstea et al 1997), p.P1007A (c.3019C>G) (Greer et al 1999), p.Q92R(c.275A>G) (Ribeiro et al 2001), and p.S940L(c.2819C>T) (Greer et al 1999). The mutations p.A1132P(c.3394G>C) and the large deletion of the promoter region and of exons 1-10 have only been described in Greek patients (included in this report as #2, #3, #7).…”
Section: Resultsmentioning
confidence: 99%
“…The cysteine-rich hydrophilic loop (aa 857-1015) is drawn oriented toward the organelle lumen. This follows the reasoning of Greer et al (35) that the corresponding Patched loop must be extracellular, as it binds the secreted signaling molecule Sonic hedgehog (38).…”
Section: Topology Of Npc1mentioning
confidence: 78%
“…As noted by Greer et al (35), the third carboxy-terminal of NPC1 harbors 19 of the 21 reported human gene mutations (11,24,35). Seven of the 13 reported missense mutations are clustered within an 88 amino acid stretch (aa 927-1015) of the cysteine-rich domain.…”
Section: Functional Analysismentioning
confidence: 88%
“…1 C and D). As suggested by its other name, "cysteine-rich domain" (24), the CTD contains eight cysteines. All cysteine residues form four pairs of disulfide bonds to stabilize the loops on the tip of this domain ( Fig.…”
Section: Resultsmentioning
confidence: 99%